(3GdeNJGQ ddaJhi aj aQhY GdMfajIs - (3YHO Gddg Hf eMehO Hf ehOhO GdehUdj GdHdOLj , eLO GdOjf CHh GdaVd,J (B683 (3g` s ((3eUWai Hf hdi s)
(3ChdgG (B:s
(3cJGH GdWgGQI (B: (3ef CQGO GdUdGI hgh eMOK adjJhVC , haQV GdhVhA ZSd GdhLg hGdjOjf eY GdeQabjf heSM QHY GdQCS hZSd GdQLdjf eY GdcYHjf s
(3BNQgG (B:s
(3hdG jONd ehdi GdehdGJ hdG ehdi Gdehdi EdG YfO YOege , hEf cGf dg ehGdi CYJbhg hCYJbge agi HGWdI hHYOg JeJ gP GdfSNI GdTQjaI HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B135 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B147 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B462s
Keywords: (3Gdabg GdMfajs